IMPACT OF GOLF COURSES ON WATER QUALITY OF BUI RIVER IN HEADWATER CATCHMENT - Thi Luong, Nguyen; Xuan Dung, Bui (Journal of Forestry Science and Technology, 2017)
This study was conducted to examine water quality of the Bui river under the impact of the Phoenix Golf Course using two main methods: macroinvertebrate community through BMWPVIET and ASPT scoring systems, along with physical and chemical parameters characteristics (pH, TSS, DO, COD, BOD5, NO3-, PO4, total coliforms) at three locations: upstream, in the stream passing through the golf course, and downstream. Measurements were taken in 4 different periods: on a sunny day without using fertilizers and pesticides, one day after applying fertilizers and pesticides, after applying fertilizers and pesticides on a rainy day, and using fertilizers and pesticides on a sunny day. The results show that: (1) pollution level decreases dramatically from upstream to downstream (from 6.4 to 4.2) based on BMWPVIET method; (2) The concentrations of pollutants increased significantly from upstream to downstream. Almost parameters exceeded B1 standard, only pH, total nitrogen and total coliform range in B1 standard limit based on Vietnam water quality Standard. WQI also depicted that water quality decreases from upstream to downstream. This paper also suggests some solutions to reduce the influence of the golf course on water quality and aquatic ecosystem of Bui River catchment including improved pesticide management and riparian buffer zones.